Pendampingan dalam Pengembangan Potensi Bonggol Jagung di Desa Blimbing sebagai Strategi Peningkatan Ekonomi - Fadila Wahyuningtyas; Mareta Elvriyana; Bhima Wahyu P; Bintang Mahendra; Kurnia Dwi Utami; Mohamad Fikri Ariqsya Rahman; Ardhia Aprilia Dewi; Aji Kusuma; Ratna Endang Widuatie (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The majority of people in Blimbing Village are farmers. One of the commodities that develops in this village is corn. The post-harvest high productivity of the corn causes corncob waste in Blimbing Village to increase every year. The problem that will be discussed in this research is the corncob waste utilization process as a mushroom growing medium which is conducted by people in Blimbing Village, Besuki Subdistrict, Situbondo Regency which few of Blimbing Village people know. Therefore, the researcher makes the innovation of corncob waste in to mushroom growing medium. Method that used in this research is planning, implementation, and evaluation method. The result of this research show that the utilization of corncob waste can be develop in to jangle mushroom growing medium, and at the same time can be an alternative to keep clean the environment from pollution, also can make Blimbing Village people more creative and increase their economic.